PEMANFAATAN MODUL ARDUINO UNTUK MENINGKATKAN HASIL BELAJAR MIKROPROSESOR KELAS XI ELIN DI SMKN 4 PARIAMAN - Muhammad Syaiful (ARKA INSTITUTE, 2022)
This event will be based on research by the learning outcomes of students who have not yet reached the KKM on subjects of microprocessors in the class XI ELIN SMK Negeri 4 Pariaman. One of the factors that influence student learning outcomes is low yet the availability of media trainers used as alternatives in learning. Therefore it needs to be done by applying the research module the arduino to see the results of student learning. This type of research was Quasi Experimental design with One Group Pretest-Posttest. The subject of this research is on grade XI ELIN SMK Negeri 4 Pariaman are registered on the academic year 2015/2016. In this research the methods of collecting data by using test results of learning in the form of an objective test consisting of a pretest and posttest. The data obtained were analyzed using the formula Gain Score. Based on the results of the study found that the average value of the pretest before the application of the Arduino module 64.48 and posttest average after the application of the arduino module of 76.55. Calculations using the gain score obtained on average an increase of 0.37 meaning has increased student learning results by category. Thus it can be concluded that the application of the arduino module can improve student learning results on subjects of microprocessors in the class XI ELIN SMK Negeri 4 Pariaman.